2017
DOI: 10.1016/j.pep.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic versus periplasmic expression of site-specifically and bioorthogonally functionalized nanobodies using expressed protein ligation

Abstract: Site-specific functionalization of nanobodies after introducing bioorthogonal groups offers the possibility to biofunctionalize surfaces with a uniformly oriented layer of nanobodies. In this paper, expressed protein ligation (EPL) was used for site-specific alkynation of the model nanobody NbBcII10. In contrast to EPL constructs, which are typically expressed in the cytoplasm, nanobodies are expressed in the periplasm where its oxidizing environment ensures a correct folding and disulfide bond formation. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…This strategy became available 30 years ago, applied to different recombinant proteins which require disulfide bonds to fold into their native structure and progressively improved with the introduction of more efficient strains such as Rosetta-gami B (DE3) or SHuffle T7 cells. These have been used for the cytoplasmic production of naked nanobodies [110,111] and of their fusion variants containing at their Cterminus an intein-chitin domain suitable for site-specific alkyne functionalization that requires reducing conditions for its functionality [109,112,113]. In one case it was confirmed that the binding properties of the non-modified nanobodies produced in the periplasm were preserved when the same binders were expressed as fusion reagents in the cytoplasm of Shuffle T7 cells [109].…”
Section: Bacterial Cytoplasmmentioning
confidence: 91%
See 2 more Smart Citations
“…This strategy became available 30 years ago, applied to different recombinant proteins which require disulfide bonds to fold into their native structure and progressively improved with the introduction of more efficient strains such as Rosetta-gami B (DE3) or SHuffle T7 cells. These have been used for the cytoplasmic production of naked nanobodies [110,111] and of their fusion variants containing at their Cterminus an intein-chitin domain suitable for site-specific alkyne functionalization that requires reducing conditions for its functionality [109,112,113]. In one case it was confirmed that the binding properties of the non-modified nanobodies produced in the periplasm were preserved when the same binders were expressed as fusion reagents in the cytoplasm of Shuffle T7 cells [109].…”
Section: Bacterial Cytoplasmmentioning
confidence: 91%
“…However, the reducing cytoplasmic conditions remain a limiting factor for the folding of the majority of VHHs [109]. An approach to overcome the shortcoming is to express the nanobodies in the cytoplasm of mutant E. coli strains that provide an oxidizing environment.…”
Section: Bacterial Cytoplasmmentioning
confidence: 99%
See 1 more Smart Citation
“…This location can be chosen strategically based on the protein's 3D structure and hence their functionality. The introduction of a “click” chemistry functional group at the C‐terminus was shown to lead to an efficient protein coupling for nanobodies (Billen et al, ; Ta et al, ). However, not all proteins will remain functional with modifications made at their termini.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, secretion of these proteins into the periplasm or culture medium leads to an increased protein solubility and stability due to a dilution of total protein content and is coupled with a reduced risk of proteolysis. In the periplasmic space, correct protein folding and, consequently, higher biological activity, is promoted by a more oxidative environment than in the cytoplasm [7] as well as by the presence of chaperones for correct folding of disulfide-bonded proteins and peptidyl-prolyl isomerases [8]. During translocation into the periplasm, N-terminal signal sequences, and methionine are removed, this leads to an authentic N-terminus of the recombinant protein, potentially avoiding negative impacts on protein activity and stability.…”
mentioning
confidence: 99%